Strategies for improving performance in long duration events: Olympic distance triathlon - Hausswirth, C.; Brisswalter, J. (Sports Medicine, 2008)
This review focuses on strategic aspects that may affect performance in a long-duration Olympic event, the Olympic distance triathlon. Given the variety of races during the Olympic Games triathlon, strategic aspects include improving technological features as well as energetics factors affecting overall triathlon performance. During the last decade, many studies have attempted to identify factors reducing the metabolic load associated (or not) with the development of fatigue process by analysing the relationship between metabolic and biomechanical factors with exercise duration. To date, a consensus exists about the benefit of adopting a drafting position during the swimming or the cycling part of the triathlon. Other potential strategic factors, such as the production of power output or the selection of cadence during the cycling or the running leg, are likely to affect the overall triathlon performance. Within this approach, pacing strategies are observed by elite athletes who swim or cycle in a sheltered position, inducing several changes of pace, intensity or stochastic shifts in the amplitude of the physiological responses. The analysis of these parameters appears to arouse some experimental and practical interest from researchers and coachers, especially for long-distance Olympic events.